United States of America. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the United States of America Delegation in 2022 are identified, focus to needs and interests of the country such as; participation in the Ninth Summit of the Americas, allowed talke about food insecurity, agriculture, climate change and recovery from the Covid pandemic, also co-organized the event entitled “CEO Summit Private-Sector Roundtable on the Food Crisis” and a panel discussion entitled “The Global Food Crisis and the Americas: Challenges and Response”, and a meeting about final policy national declaration, named “Our Sustainable Green Future”; it took part in three major plenary and panel events at the World Food Prize Foundation’s Borlaug Dialogue; provided robust technical and logistical support for major activities related to the control and prevention of African Swine Fever (ASF); it established new strategic partnerships to foster the sharing of knowledge and resources to drive agricultural development in the hemisphere; it has accommodated the Regional Fund for Agricultural Technology (FONTAGRO), providing administrative and strategic support to familiarize the organization with the rules and procedures of the Institute.